What is the most effective technique and composite for bonding aligner attachments to primary enamel? - TOZLU, MURAT (My University, 2024)
Objectives: This in vitro study evaluated the shear bond strength (SBS) of aligner attachments bonded to primary teeth with different techniques and composites. Material and Methods: Eighty attachments were prepared using five composites: An aligner composite (GC aligner connect [GAC]), two flowable restorative composites (G-aenial universal injectable and Estelite universal super low flow), and two one-step orthodontic composites integrated with primer (GC ortho connect flow and GC ortho connect). Aligner and restorative composites were applied with self- or total-etch (SE or TE) modes of universal adhesive (G-Premio Bond). Self-adhering composites integrated with primer were applied after acid etching. Excessive composites were removed with tungsten carbide burs after the polymerization of resin attachments. All primary teeth were exposed to thermocycling. Bond strength was determined with a universal testing machine. Remnant resin attachment was scored with the resin attachment remnant index. Kruskal–Wallis, Mann–Whitney, and Chi-square tests were used for statistical analyses. Results: The self-etching technique demonstrated lower SBS values compared to total-etching and self-adhering groups regardless of composite type. The highest SBS was found with aligner composite (GAC) and the total-etching technique. Self-adhering composites showed sufficiently high SBS values comparable with GAC and TE bonding techniques. The amount of remnant attachment was significantly higher in the total-etching and self-adhering groups compared to SE bonding with GAC (P < 0.05). Conclusion: Self-adhering orthodontic composites can be preferred to simplify the bonding of aligner attachments to primary enamel after acid etching. Keywords: Aligner, Attachment, Bonding, Primary teeth
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Diş Hekimliği Oral Cerrahi Ve Tıp; Clinical Medicine (Med); Clinical Medicine; Dentistry Oral Surgery & Medicine; Ortodonti; Orthodontics; Aligner; Attachment; Bonding; Primary teeth